PELAKSANAAN PELAYANAN PUBLIK DAN TRANSPARANSI INFORMASI DI DESA SEBERANG TALUK PADA TAHUN 2018 - Meizi Hardianto; Erman M (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research is motivated by the stipulation of law number 23 of 2014 concerning Regional Government, the administration of government in the regions, especially regencies/cities, is carried out according to the principle of autonomy as wide as possible in the system and principles of the Unitary State of the Republic of Indonesia. The implementation of such regional government is then more familiarly called regional autonomy. Regional autonomy is the right, authority, and obligation of the autonomous region to regulate and manage its own government affairs and the interests of the local community in accordance with laws and regulations. The problem in this study is how to implement the services of the Seberang Taluk Village Head in Public Services and Information Transparency in 2018 The purpose of this study was to determine the implementation of the services of the Seberang Taluk village head in public services and information transparency. The method used in this research is qualitative with a three-format approach, namely descriptive, verification, grounded research then the research informants are 8 people, while the technique used in sampling is the purposive sampling technique, namely the sampling technique is based on a specific goal (the chosen person). really have the criteria as a sample) The results showed that the implementation of the services of the Seberang Taluk Village Head in Public Services and Information Transparency in 2018 basically went well. However, there are several obstacles that arise in the implementation of Information Services and Public Transparency in 2018 researchers see that the lack of participation from the community in the implementation or distribution of village fund placement allocations, does not take part in village meetings and the community does not know for sure what types of assistance will be provided. expelled from the village. So that the implementation of Public Services and Transparency of Information in 2018 has not been optimal in one of these villages. Keywords: Public Service And Information Transparency.